PEMIKIRAN ISLAM PROGRESSIF: Dua Dekade Pemikiran dan Gerakan Jaringan Islam Liberal (JIL) - A. Ilyas Ismail (Jurnal Theologia, 2012)
Theologically, Islam is one (single) and absolutely true. However, historically, after being understood, and translated into the reality of life in the dimensions of space and time, Islam is not a single, but wide in variety or has plural form and manifest in at least three schools of thought, the traditional Islamic revivalist Islam (fundamentalism), and Islam liberal (progressive). Group of the Liberal Islam Network (JIL) represents the latter mindset. Although it is relatively young, only 10 years old, JIL became popular because it brings new ideas that often arouse controversy in the community. The progressive thoughts carried out by JIL concerning the four areas. First, the reformation in politics, JIL forwards the idea of secularism. Second, in the field of social reforms and civic religion, JIL brought the idea or concept of pluralism. Third, reforms in individual freedom, JIL put forward the idea of liberalism both in thought and action. Fourth, reforms in the field of women, JIL brought the idea of gender equality. These thoughts get some pros and cons in the community. Some denounce and condemn it, but others appreciate and support it. In such an atmosphere, JIL continues to grow as a progressive Islamic thought and movements in Indonesia.Secara teologis, Islam adalah satu (tunggal) dan mutlak benar. Namun, secara historis, setelah dicoba dihayati, dipahami, dan diterjemahkan dalam realitas kehidupan dalam dimensi ruang dan waktu, Islam tidak tunggal, tetapi beragam alias plural yang mewujud dan mengejawantah setidak-tidaknya dalam tiga aliran pemikiran, yaitu Islam tradisional, Islam revivalis (fundmentalisme), dan Islam liberal (progresif). Kelompok Jaringan Islam Liberal (JIL) mewakili pola pemikiran yang terakhir. Meski usianya relative muda, baru 10 tahun, JIL menjadi popular karena mengusung pemikiran-pemikiran baru yang sering memunculkan kontroversi dalam masyarakat. Pembaharus pemikiran yang diusung JIL menyangkut empat bidang. Pertama, pembaruan dalam bidang poiitik. Di sini, JIL mengedepankan gagasan sekularisme. Kedua, pembaruan dalam bidang social agama dan kemasyarakatan. Di sini, JIL mengusung ide atau konsep pluralisme. Ketiga, pembaruan dalam kebebasan individu. Dalam hal ini, JIL mengedepankan gagasan liberalism baik dalam berpikir maupun bertindak. Keempat, pembaruan dalam bidang perempuan. Di sini JIL mengusung ide kesetaraan gender. Pemikiran pembaharuan JIL ini mendapat pro dan kontra dalam masyarakat. Sebagian mencela dan mengecamnya, tetapi sebagian lagi memberi apresiasi dan mendukungnya.Dalam suasan semacam itu, JIL terus tumbuh sebagai pemikiran dan gerakan Islam progresif di Indonesia.